EFL Education And Teacher Developments: The Implementation Of CLC And Teachers’ Teaching Style Preference - Nasmah Riyani (STAI Miftahul Ula Nganjuk, 2017)
Teachers’ teaching style preferences is undoubtedly being an essential thing in dynamic classroom language teaching. This study aimed to investigate Indonesian EFL teachers’ teaching style and their beliefs in the implementation of communicative language competence. Additionally, this study also explored students’ speaking competence. Fifty teachers were involved based on purposive sampling from one of regency of the Capital city, Kolaka Indonesia. The respondents cooperatively supported the study, then they filled Grasha (1996) Teaching Style Inventory (TSI). The descriptive statistic showed that the respondents mostly implement formal authority styles and personal model respectively. The students’ speaking competence was still categorized low. Regarding the nominal preference of authority styles, since the purpose of language teaching on basis of curriculum based teaching, the teacher believed that giving students space to explore their flexibility in communicating would not help them to pass the national examination